PENGARUH SISTEM OLAH TANAH DAN WAKTU PENYIANGAN PADA HASIL TANAMAN JAGUNG (Zea mays L.) - Muhamad Noor Azizu (Media Agribisnis, 2020)
The presence of disturbing plants in the cultivation process of corn plants will respond to the corn crop yields. The presence of disturbing plants can cause competition in the photosynthesis process. In essence, weed control is to suppress the population. The purpose of this study was to examine the effects of tillage patterns and time of weeding on maize crop products and to obtain a combination of tillage patterns with appropriate weeding times for corn planting. The experiment was conducted from February to June 2020 at the Buton UMU Research Experimental Garden. Laboratory analysis was carried out in the integrated laboratory of the Faculty of Agriculture and Animal Husbandry of UMU Buton. The experiment was arranged in a split-plot design (RPT) with three replication. main plots were tillage system consists of three levels., (1) T1 = zero tillage; (2) T2 = minimal tillage; and (3) T3 = maximum tillage. Subplots were a time of weeding consists of four levels., (1) P1 = no weeding; (2) P2 = weeding 21 days after planting; (3) P3 = weeding 21 and 42 days after planting; and (4) P4 = weeding 21, 42 and 63 day after planting. The results showed that the appropriate combination of T1 and T4 treatment would produce better maize/plant weight and corn seed yields of 6.27 tonnes ha-1, whereas for T2 and T3 it did not require weeding time with yields respectively maize harvest was 5.84 tonnes ha-1 and 5.83 tonnes ha-1 Keywords: konservasi, gulma, jagung